Design of a Patterned Diamond Substrate for Ordered Neural Cell Adhesion. (2015) - Tong, Wei; Fox, Kate; Ganesan, Kumaravelu; Prawer, Steven
Abstract: Diamond has recently attracted lots of interest as a potential candidate for neural interface due to many of its advantages such as biocompatibility, superior hardness and chemical inertness. Here we present a method for designing and fabricating a diamond platform for ordered neural cell adhesion. Microcontact printing was used for selective nanodiamond seeding and chemical vapor deposition was conducted subsequently to form diamond patterns. We compared different printing methods and precise microsized patterns were finally fabricated for the formation of ordered neural cell network.